2004
DOI: 10.1108/96754260480001036
|View full text |Cite
|
Sign up to set email alerts
|

Selection techniques within the accountancy profession in Scotland

Abstract: The ever‐increasing cost of seeing a graduate training contract through to its successful completion has made the selection decision, and indeed the choice of selection techniques used, increasingly vital. This paper identifies the selection methods currently used by the Scottish accountancy profession to recruit graduate trainees, compares these against best practice and highlights a number of areas where improvements to current practice would be recommended. Analysis of the selection literature revealed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Interpersonal and communication skills are skills, which enable accountants to effectively work with each other, allow information to be received and transmitted effectively and reasoned judgement and effective decisions to be made (IFAC, 2010). Research has confirmed the importance of being able to work effectively with others (Berry, 1993;Ravenscroft, 1997;Arquero et al, 2001;Hassall et al, 2003;Gammie et al, 2004;ACCA, 2008;Kavanagh and Drennan, 2008;Hancock et al, 2009;Jackling and de Lang, 2009;Crawford et al, 2011, Howecraft, 2017. Furthermore, team working was identified as one of the most important skills sought by ICAS employers when recruiting graduate trainees (Gammie et al, 2004).…”
Section: Interpersonal and Communication Skillsmentioning
confidence: 97%
See 2 more Smart Citations
“…Interpersonal and communication skills are skills, which enable accountants to effectively work with each other, allow information to be received and transmitted effectively and reasoned judgement and effective decisions to be made (IFAC, 2010). Research has confirmed the importance of being able to work effectively with others (Berry, 1993;Ravenscroft, 1997;Arquero et al, 2001;Hassall et al, 2003;Gammie et al, 2004;ACCA, 2008;Kavanagh and Drennan, 2008;Hancock et al, 2009;Jackling and de Lang, 2009;Crawford et al, 2011, Howecraft, 2017. Furthermore, team working was identified as one of the most important skills sought by ICAS employers when recruiting graduate trainees (Gammie et al, 2004).…”
Section: Interpersonal and Communication Skillsmentioning
confidence: 97%
“…Research has confirmed the importance of being able to work effectively with others (Berry, 1993;Ravenscroft, 1997;Arquero et al, 2001;Hassall et al, 2003;Gammie et al, 2004;ACCA, 2008;Kavanagh and Drennan, 2008;Hancock et al, 2009;Jackling and de Lang, 2009;Crawford et al, 2011, Howecraft, 2017. Furthermore, team working was identified as one of the most important skills sought by ICAS employers when recruiting graduate trainees (Gammie et al, 2004).…”
Section: Interpersonal and Communication Skillsmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite recent innovations in accounting education, this field continues to be criticised on the grounds that its technical content encourages rote learning (Gammie et al , 2010; Turner and Baskerville, 2013; Phillips and Graeff, 2014; Bayerlein and Timpson, 2017; Moilanen, 2017). This narrow focus results in accounting graduates who are ill-equipped to face the challenges of a changing business environment driven by factors such as globalisation, ongoing technological advances, increasing and rapidly changing regulations, increased focus on environmental, social and governance issues and evolving markets (Mohamed and Lashine, 2003; Gammie et al , 2010; Watty et al , 2014). For example, “new global business models and the digital age” (Jackling and De Lange, 2009, p. 371) have transformed the role of the accountant from simply preparing financial information to analysing and interpreting it (Ballantine and McCourt Larres, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An extensive international literature reviews the extent to which soft skills have been incorporated into university accounting education (see, for example, Boyce et al , 2001; Crebert et al , 2004; de Villiers, 2010; Gammie et al , 2010; Barac and du Plessis, 2014). Included in this literature are the innovative learning methods used to develop soft skills.…”
Section: Introductionmentioning
confidence: 99%